Brokeback mountain. - Prieto, Rodrigo (Quezon City : Viva Video, 2006)
A sweeping epic that tells the story of two young men, Ennis (Health Ledger), a ranch-hand and Jack (Jake Glyllenhad). a rodeo cowboy meet in the summer of 1963 while working in a local ranch, and unexpectedly forge a lifelong connection, one whose complications, joys and tragedies provide a testament to the endurance and power of love. They struggle to keep their bond alive through their own marriages, through children, and through the mighty grip of societal confines and the expectations of what it is to be a man.